Accounting for biodiversity: a systematic literature review - King, Timothy; King, Tatiana (Emerald, 2026)
Purpose Following a recent worldwide regulatory push to improve the identification, assessment and disclosure of climate and, more narrowly, biodiversity risks, this paper provides a timely review of the state-of-the-art of literature on biodiversity. Design/methodology/approach We employ a systematic literature review. The final corpus comprises 120 academic papers published in accounting, finance, economics and management journals ranked in the Academic Journal Guide (AJG) from 2021 to 2024. From this, we identify five thematic clusters and critically analyze how biodiversity is conceptualized, measured, disclosed and financialized in the literature. Findings Our review reveals that biodiversity accounting is still at an embryonic stage. Despite new regulations, an ongoing challenge is linked to the difficulty in establishing what constitutes biodiversity from a firm perspective and what data should be collected, how it should be reported, disclosed and verified. Research limitations/implications Further research is required to support the efforts of policymakers to ensure firms can better capture biodiversity-related risks and impacts, while also examining the assurance and reporting mechanisms that can support credible disclosure. Originality/value Our paper makes several contributions. First, we provide the most up-to-date synthesis of interdisciplinary research in the fields of accounting, finance, economics and management. Second, we identify tensions that arise when accounting logic of comparability, aggregation and periodic reporting faces the complexity and context-specific biodiversity information. Third, we develop a future research agenda that links biodiversity measurement choices to recognition, accountability and assurance debates in accounting research.
Keywords: Biodiversity; Reporting; Biodiversity loss; Climate accounting; Literature review; fi=Rahoitus|en=Finance|; fi=Laskentatoimi|en=Accounting|